EKSPLORASI DAN ISOLASI BAKTERI RHIZOBIUM TUMBUHAN LEGUMINOSA DI LAHAN BERGAMBUT KAMPUS UIN SUSKA RIAU PEKANBARU - R. Danang Suto Pamungkas; Mokhamad Irfan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Rhizobium is a group of soil bacteria that is able to fixing nitrogens from the atmosphere throught symbiosis mechanism with legumes. It has an important role as a provider of nutrients the plants. Regarding of the fact, this research was aimed to isolate the Rhizobium from root nodules of legumes in peatland areas of State Islamic University of Sultan Syarif Kasim Riau. The Rhizobium isolation was conducted in Laboratory of Pathology Entomology and Microbiology of Faculty of Agriculture and Animal Science. The root nodules of legumes were selected and sterilized using 10 % disinfectant solution for 2 minutes before isolated. The Rhizobium colonies were isolated on Nutrient Agar (NA) media. The results showed there were nine isolates of Rhizobium to be isolated. Macroscopic of the colonies showed there were eight isolates of translucen (white-milk) and one isolate was yellowish-white, with spherical on shape, flat edges, convex surface, and sticky textures of colonies. Microscopic of cells were gram-negative bacill with varies of size i.e. 0.42 ± 0.19 µm to 1.075 ± 0.425 µm of length and 0.25 ± 0.03 µm to 0.6 ± 0.15 µm in width. The Rhizobium isolates of Clitoria laurifolia, Acacia sp., and Albizia sp. were three fastest in growth.